ANALISIS PENGARUH PRODUK, HARGA, TEMPAT, PROMOSI DAN E-QUALITY SERVICE TERHADAP KEPUTUSAN PEMBELIAN DI ZARA CENTRAL PARK PADA MASA PANDEMIC COVID-19 - Agus Wahyono (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2021)
This study aims to determine the effect of Promotion, Price, Location, Promotion, and E-service quality on purchasing decisions of Zara Central Park Mall partially or simultaneously. The data used are primary data collected through distributing questionnaires to 100 respondents who have visited and purchased at Zara Central Park Mall. The method used in this study is a quantitative method and the results of the study are based on respondents' answers using a Likert scale. The data analysis method used in this study is the Multiple Linear Regression Test, F test, t test and the coefficient of determination. The results showed that simultaneously (F test) there was a significant influence between Product (X1), Price (X2), Location (X3) Promotion (X4), E-service quality (X5) variables on Purchasing Decisions (Y). Partially (t test) Product and Price have a significant effect on purchasing decisions, while Location, Promotion and E-service quality do not have a significant effect on purchasing